Investigation of the battery degradation impact on the energy management of a fuel cell hybrid electric vehicle - Ghaderi, Razieh; Kandidayeni, Mohsen; Soleymani, Mehdi; Boulon, Loic (IEEE, 2020)
This paper studies the influence of battery degradation over the performance of a fuel cell hybrid electric vehicle (FCHEV). For this purpose, an optimized fuzzy strategy based on the costs of battery and fuel cell degradations as well as fuel consumption and battery recharging is employed. Simulations are done by two driving cycles for three scenarios based on battery state of health (SOH) and validity of feedback signal. Simulation results prove that battery aging has a considerable impact on the total cost of a FCHEV. Moreover, tuning of the EMS parameters according to the battery SOH decreases the defined cost.
Keywords: Fuel consumption; Battery degradation; Optimization; Energy management system; Fuel cell hybrid electric vehicle